Haida grave totem poles and carvings, Howkan village, Long Island, Alaska, ca. 1900 - Hegg, Eric A., 1867-1948
Several totem poles and other carvings (bear, orca) in graveyard, Howkan, Alaska, ca. 1898-1902. Notes from unidentified source: Totem poles and graveyard at Howkan Alaska